The clinical characteristics, and sociodemographic variables, in alcohol dependence - Mırsal, Hasan; Kalyoncu, Ayhan; Pektaş, Özkan; Mırsal, Nursel; Beyazyürek, Mansur (Journal of Dependence, 2000)
Alcohol dependence arises approximately in five years after the starting time to alcohol cnsumption. But it may take 15-20 years until seeking for any kind of treatment for alcohol dependence. It seems difficult to define the causes of the long time span. The aim of this study is retrospectively to investigate development of alcohol dependence with respect to sociodemographical variables, alcohol use and other clinical features. Twentyfive hospitalized patients who did not have another psychiatric disorder and receiving treatment for the first time were included to the study. The subjects were hospitalized between December 1998 and March 1999. The patients were evaluated with a semi stuructured interview form and Michigan Alcoholism Scanning Test. The patient group consisted of 2 (8%) female and 23 (92%) male individuals. The mean age of subjects was 44.2 (sd=10.1). The average starting age to alcohol was 18.8 year (sd=4.4), the average time of alcohol use was 25.3 year (sd=10.4. The time period for developing alcohol dependence was 8.2 (sd=4.5) year and the time spent since the first use of alcohol to first application for treatment was 17.0 (sd=9.6) year. The mean latency until alcohol was considered as a problem by patients was 5 (sd=6.4) years and tolerance was 8.2 (sd=4.8) fold. the mean score of Michigan Alcoholism Scanning Test (MAST) was 20.2(ss=6.2). We can conclude from thi study that rather a long time is spent until receiving treatment for alcohol dependence. These results indicate that larger number of patient and more detailed investigation are needed to evaluate the variables which influence the application process for treatment .